Aerobic Bacterial Conjunctival Flora in Diabetic Patients - Saeed Iqbal, Manzoor A. Mirza, Tahir Masaud Arbab, Saleem Qadeer (Pakistan Journal of Ophthalmology, 2010)
Purpose: To study the aerobic conjunctival flora of diabetic patients and its relation to the presence and level of diabetic retinopathy and the duration of the disease. Material and Methods: 80 patients form Sir Syed Diabetic Clinic with no evidence of ocular surface disease were included. These diabetic patients were compared with 50 nondiabetic subjects. All patients underwent slit-lamp evaluation, conjunctival scrapings, and indirect ophthalmoscopy. Results: The frequency of positive conjunctival cultures was significantly higher in the diabetic group than in nondiabetic group (95% vs. 72%, p<0.001). Among diabetic patients, a significantly higher frequency of positive cultures was detected in those with diabetic retinopathy than those without retinopathy (p=0.001). Neither the duration of the diabetes nor the hypoglycemic therapy correlated with the culture results. Staphylococcus epidermidis was the most common microorganism isolated, and its identification was more frequent in patients with retinopathy than those without diabetic retinopathy. Conclusion: Diabetic patients have a significantly higher number of positive conjunctival cultures. The presence of diabetic retinopathy was correlated with an increase in positive cultures and a higher proportion of Staphylococcus epidermidis.